Perversion : the erotic form of hatred - Stoller, Robert J. (Maresfield library., 1986)
The main contention is that in perversion the main clinical factor is hostility. It combines with sexual desire to produce the various forms that perversion can take on. Stoller shows that the perverse scene aims not only at denying castration, but also at securing a more solid basis for a jeopardized sexual identity. Risk, vengeance and trauma are some of the ideas that the author discusses while building up his argument.